EFISIENSI BEBERAPA MODEL TUNGKU - Djeni Hendra; Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The result of investigation of cook stove designs from Palembang, Yogyakarta and Bogor is reported in this paper. Fuel wood used were : Acacia mangium, Acacia auriculiformis and Leucaena glauca.The result shows that the dry wood consumption for high power phase ranges from 0,31 - 0,43 kg, dry wood consumption for low power phase ranges from 0,01 - 0,42 kg, high power phase from 6,12 - 13,23 KW, low power phase from 0,17- 2,98 KW, wood standard consumption from 0,20 - 0,25 kg wood/kg water, flexibility from 2.51 - 21,86 and efficiency ranges from 12,42 - 24,79 %.